Interação leitura e escrita: processos de leitura de perguntas de exame revelados pela escrita das respostas - Cabral, Ana Lúcia Tinoco (2005)
The area of the following work is lecture and writing and it has as subject matter reading comprehension processes of exam s questions by their writing answers. I admit as hypothesis that it is possible to establish strategies that allow analyzing reading processes using only the written produced from the reading of a text. My purpose on this work is to elaborate strategies to investigate reading processes by exploring together the text of a exam question and the writing of its answers. For the achievement of the proposed goals, I went through the principles of the Psycholinguistics postulated by Le Ny (2005) and Coirier, Gaonac h & Passerault (1996), and the principles of Textual Linguistics postulated by van Dijk (1977, 1980 e 1996), Kintsch (1998) and van Dijk & Kintsch (1983) mainly. I justify my work basing on the originality of corpus and of the strategies of analysis. The is composed of a question of the OAB exam and twenty answers to it, this type of corpus has never been used in research on processes in reading before. As strategies of analysis used, I established eight topics, corresponding to seven operations of reading processes and the construction of mental representation. I analyzed first the exam question text, then the written linguistic marks of reading processes of the question revealed by the written answers. The research done made possible to prove my hypothesis and achieve my goals. In addition, the work pointed out new perspectives to reading comprehension studies, especially concerning the importance of linguistic knowledge on reading processes